Raid the Icebox 1 with Andy Warhol : An Exhibition selected from the storage vaults of the Museum of Art, Rhode Island School of Design. - Robbins, Daniel; Bourdon, David; Ostrow, Stephen E.; Institute for the Arts, Rice University, Houston; The Isaac Delgado Museum, New Orleans (Providence : Museum of Art, Rhode Island School of Design, 1969)
Warhol, Andy ; Cezanne, Paul ; Feininger, Lyonel ; Lam, Wifredo ; Mac Entyre, Eduardo ; etc.
Raid the Icebox 1 with Andy Warhol : An Exhibition selected from the storage vaults of the Museum of Art, Rhode Island School of Design, Institute for the Arts, Rice University, Houston, October 29, 1969 - January 4, 1970 ; The Isaac Delgado Museum, New Orleans, January 17 - February 15, 1970 ; Museum of Art, Rhode Island School of Design, Providence, April 23 - June 30, 1970
boek